2011
DOI: 10.1175/2010jcli3939.1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of North Pacific Tropical Cyclone Activity by Three Phases of ENSO

Abstract: Tropical Pacific Ocean warming has been separated into two modes based on the spatial distribution of the maximum sea surface temperature (SST) anomaly: an east Pacific warming (EPW) and a central Pacific warming (CPW). When combined with east Pacific cooling (EPC), these three regimes are shown to have different impacts on tropical cyclone (TC) activity over the North Pacific by differential modulation of both local thermodynamic factors and large-scale circulation patterns. In EPW years, the genesis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
180
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(206 citation statements)
references
References 39 publications
26
180
0
Order By: Relevance
“…The variations of TC genesis frequency and intensity in the WNP, from intraseasonal to interdecadal time scales, are related to ISO phases (e.g., Gray 1979;Huang et al 2011;Li and Zhou 2013;, monsoon trough variability (e.g., Ritchie and Holland 1995;Chen et al 2004;Wu et al 2012), the El Niño-Southern Oscillation (e.g., Chan 2005;Du et al 2011;Kim et al 2011), and the PDO (e.g., Yang et al 2012;Liu and Chan 2013). WNP TC genesis frequency depends on the ISO phase ) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
“…The variations of TC genesis frequency and intensity in the WNP, from intraseasonal to interdecadal time scales, are related to ISO phases (e.g., Gray 1979;Huang et al 2011;Li and Zhou 2013;, monsoon trough variability (e.g., Ritchie and Holland 1995;Chen et al 2004;Wu et al 2012), the El Niño-Southern Oscillation (e.g., Chan 2005;Du et al 2011;Kim et al 2011), and the PDO (e.g., Yang et al 2012;Liu and Chan 2013). WNP TC genesis frequency depends on the ISO phase ) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
“…Collins and Mason (2000) showed that eastern North Pacific tropical cyclone statistics were different in the far eastern North Pacific (east of 116º W) compared with the region west of 116º W. Other analyses also indicate that the seasonal track distribution of tropical cyclones responds to longitudinal variations in ocean temperature anomalies, even if the total seasonal number of storms might not (Irwin and Davis, 1999;Kim et al, 2011).…”
mentioning
confidence: 99%
“…Here the author has paid attention to the forecast during El Nino or La Nina episodes while we also have to predict for the neutral phase; therefore, many studies on forecasting cyclones season have further analysed the relationships between climate factors and other circulations not related to ENSO. For example, one of the important factors in predicting seasonal cyclones in Northwest Pacific region is a factor regarding the Western North Pacific Subtropical High often reflected in some layers of the atmosphere on regional circulation in the region [15][16][17][18][19][20][21][22][23][24][25] • N, 115-150 • E. Cyclones cannot occur in the subtropical high-pressure area of Northwest Pacific. Subtropical high pressure in the Pacific northwest region, when intensifying and encroaching the west land, will block the cyclone from sweeping north and west, so in these cases, cyclones tend to land more inclined on the west coast.…”
Section: Relationship Between Enso and Cyclone Activitiesmentioning
confidence: 99%
“…In [17], Kim and colleagues suggest that the warming of the Pacific sea is divided into two distinct modes according the spatial distribution of the sea surface temperature turbulence: warming in the Eastern Pacific (EPW) and warming in the central Pacific (CPW). The 3rd mode is the cooling of the sea surface temperature in the Eastern Pacific region (EPC).…”
Section: Relationship Between Enso and Cyclone Activitiesmentioning
confidence: 99%